Why Are There So Many Ways to Measure Pain? Epistemological and Professional Challenges in Medical Standardization - Hanna Grol-Prokopczyk (Qualitative Sociology Review)
Pain is a profoundly subjective phenomenon, which remains largely impenetrable to the tools of biomedicine. How, then, do pain researchers—specifically, quantitative medical researchers whose work is predicated on transforming pain into numbers—measure pain in their studies? How do they select and justify specific measures, and does this process lead to measurement standardization? This article analyzes 79 published medical studies about low back pain (LBP) and 20 interviews with pain experts (including 15 with authors of the reviewed studies) to address these questions. Findings reveal that LBP researchers use an extremely diverse set of outcome measures in their studies, typically based on patient self-report. The subjectivity and interpersonal incomparability of self-reports are widely acknowledged but treated as largely unproblematic—a matter of acceptable measurement error rather than “epistemological purgatory” (Barker 2005). However, researchers frequently disagree on what constitutes a “pain measure.” Many respond to the considerable challenge of treating pain intensity by redefining their work—sometimes in the face of resistance from patients—around other, putatively more treatable domains, such as disability. The diverse, arguably unstandardized approaches to measuring pain appear attributable less to pain’s epistemological fragility than to its therapeutic intractability, and to the medical community’s diffuse social structures and professional goals.